The third occurrence of plagiarism - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
As per the quality policy - AJP uses active plagiarismcheck tools and submits articles to the researchers having best matching work for refereeing; still a few cases have managed to pass all the filters. The third case (since inception of the journal) of plagiarism has just been unearthed by Dr Atmaram Pawar.